Preventive Antepartum Care - William J. Ledger (Hindawi Limited, 1994)
As the role of the obstetrician-gynecologist evolves to include primary care, the obstetrician must assume greater responsibility for providing prenatal preventive care, particularly regarding the STORCH5 pathogens.